In vitro antimicrobial activity of irreversible hydrocolloid impressions against 12 oral microorganisms Atividade antimicrobiana in vitro de moldes de hidrocolóide irreversível contra 12 microrganismos orais - Luciana Assirati Casemiro; Fernanda de Carvalho Panzeri Pires-; Heitor Panzeri; Carlos Henrique Gomes Martins; Isabel Yoko Ito (Sociedade Brasileira de Pesquisa Odontológica, 2007)
This study evaluated in vitro the antimicrobial activity of irreversible hydrocolloids (one containing an antimicrobial agent) prepared with water or with a 0.2% chlorhexidine digluconate solution against 12 strains of the oral microbiota. Twenty specimens (0.5 x 1.0 cm) for each group (1. Jeltrate mixed with water; 2. Jeltrate mixed with 0.2% chlorhexidine digluconate solution; 3. Greengel mixed with water; 4. Greengel mixed with 0.2% chlorhexidine digluconate solution) were prepared under sterile conditions and placed in culture media inoculated with the indicator strains. After incubation in aerobiosis or microaerophilia, inhibition of the microbial growth was measured and the results were interpreted. The normal adherence curve revealed a non-normal distribution of the data, so the non-parametric Friedman Test was performed (p < 0.05). The antimicrobial activity of the groups was classified in the following order: 1, 3, 4, and 2. The results suggest that the method of preparing irreversible hydrocolloids with a 0.2% digluconate chlorhexidine solution is more effective than the incorporation of an antimicrobial agent in the powder to reduce cross-contamination caused by impressions. Este trabalho avaliou in vitro a atividade antimicrobiana de alginatos (um deles contendo agente antimicrobiano) manipulados com água ou solução de digluconato de clorexidina a 0,2% contra 12 cepas da microbiota oral. Vinte espécimes (0,5 x 1,0 cm) para cada grupo (1. Jeltrate manipulado com água, 2. Jeltrate manipulado com solução de digluconato de clorexidina a 0,2%; 3. Greengel manipulado com água; 4. Greengel manipulado com solução de digluconato de clorexidina a 0,2%) foram confeccionados sob condições estéreis e semeados em meios de cultura inoculados com as cepas indicadoras. Após incubação em aerobiose ou microaerofilia, a inibição do crescimento microbiano foi medida e os resultados foram interpretados. A curva normal de aderência revelou uma distribuição não-normal dos dados, então o teste não paramétrico de Friedman (p < 0,05) foi realizado. A atividade antimicrobiana dos grupos foi classificada na seguinte ordem crescente: 1, 3, 4 e 2. Os resultados sugerem que a manipulação de alginatos com solução de digluconato de clorexidina a 0,2% é um método efetivo para reduzir a contaminação-cruzada causada pelos moldes, mais que a incorporação do agente antimicrobiano no pó.